2019
DOI: 10.1038/s41598-019-43572-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells undergoing EMT are poorly correlated with clinical stages or predictive of recurrence in hepatocellular carcinoma

Abstract: Experimental and clinical studies have highlighted that circulating tumor cell (CTC) with phenotypic hallmarks of epithelial-mesenchymal transition (EMT) plays a critical role in the metastatic and recurrence of solid malignancy. Here we retrospectively evaluated the presence of CTC and its EMT phenotypes in hepatocellular carcinoma (HCC) patients and investigated their clinical relevance. We optimized the Canpatrol TM CTC analysis system to enumerate CTC and classify EMT phenotypes in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 39 publications
0
61
0
Order By: Relevance
“…Although serial monitoring of cell-free DNA was common, almost all reported CTC studies did only one to two measurements of CTC. For example, CTC counts have been used in previous studies for determining the diagnosis and assessing the prognosis of patients with HCC [15][16][17][30][31][32]. A correlation exists between the postoperative early recurrence of HCC and mesenchymal CTCs [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although serial monitoring of cell-free DNA was common, almost all reported CTC studies did only one to two measurements of CTC. For example, CTC counts have been used in previous studies for determining the diagnosis and assessing the prognosis of patients with HCC [15][16][17][30][31][32]. A correlation exists between the postoperative early recurrence of HCC and mesenchymal CTCs [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, CTC counts have been used in previous studies for determining the diagnosis and assessing the prognosis of patients with HCC [15][16][17][30][31][32]. A correlation exists between the postoperative early recurrence of HCC and mesenchymal CTCs [32,33]. An elevated number of CTCs is associated with unfavorable clinicopathologic characteristics responsible for poor prognosis in patients with HCC [34].…”
Section: Discussionmentioning
confidence: 99%
“…Aneuploidy-induced cell state transitions may be a novel cause of the strong correlation between aneuploidy and death from cancer. Additionally, recent evidence has underscored the importance of phenotypic plasticity in the metastatic cascade and has suggested that an EMT is neither a necessary nor an irreversible step in cancer cell dissemination (Chen et al 2019;Padmanaban et al 2019;Zheng et al 2015;Fischer et al 2015;Liu et al 2019). Instead, cancer cells can lose certain epithelial characteristics to promote migration out of the primary tumor site and into circulation, but they can re-establish them (through a mesenchymal-epithelial transition) in order to colonize a distant location (Dongre and Weinberg 2019).…”
Section: Discussionmentioning
confidence: 99%
“…EMT is considered as one of the key mechanisms of invasion and metastasis of lung cancer. [ 6 ] Therefore, the detection and analysis of interstitial CTCs in lung cancer is of great value clinically.…”
Section: Introductionmentioning
confidence: 99%